Politic through da’wah on facebook: exploring da’wah strategy in women’s political communication - Riauan, Muhd Ar.Imam; Prihatin, Panca Setyo; Muhlis, Muhlis; Tengku Azzman, Tengku Siti Aisha (Communication Science Department. UIN Sunan Kalijaga Yogyakarta, 2022)
Da'wah activities are not only carried out by preachers; Muslim politicians who have a verified (?) Blue Tick Facebook account have the opportunity to carry out Da'wah activities on Facebook. This study aims to explore Bil-Haal's Da'wah and Bit-Tadwin's Da'wah on Intsiawati Ayus' political Communication as a Women politician who has persisted in representing the people as members of the DPD RI since the 2004 Elections to 2019. The research method uses the Krippendorf qualitative content analysis with a pragmatic form of content analysis which classifies signs related to Bil-Haal Da'wah and Bit-Tadwin Da'wah. In this study, 26 Facebook posts were analyzed from an influential female politician in Indonesia. The results of this study indicate that women politicians carry out Bil-Haal Da'wah and Bit-Tadwin Da'wah. Da'wah Bil-Haal shows da'wah activities that the community can imitate. Bit-Tadwin's da'wah is a da'wah that is carried out by writing on social media.